PENGARUH BUDAYA ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR KEPALA DESA BANTARJATI KECAMATAN KERTAJATI KABUPATEN MAJALENGKA - Deni Herdiana; Detri Kurnia Nugraha (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
This research is motivated by a problem related to the quality of public services caused by organizational culture. The formulation of the problem in this study is aimed at knowing how organizational culture, the quality of public services and how much influence organizational culture has on the quality of public services at the Bantarjati Village Head Office. This research data consists of primary and secondary data obtained through direct research in the field. The population in this study consisted of 57 people and 50 people were taken as a sample, with a precision value of 95%. While the data analysis technique in this study, namely using quantitative methods with a descriptive-quantitative approach. The results of this study indicate that the organizational culture and quality of public services are descriptively rated as good. While quantitatively the results of this study indicate that there is a strong positive effect of organizational culture on the quality of public services, which when percented the value is 57.5% and the remaining 42.5% is influenced by other factors outside the organizational culture variable. In general, the conclusion of this study is that the application of a good organizational culture will empirically have a positive impact on the quality of public servants at the Bantarjati Village Office, Kertajati District, Majalengka Regency